2011
DOI: 10.1007/s12028-011-9639-z
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Related Effects of Adenosine Triphosphate-Activated Microglia on Pro-Inflammatory Factors

Abstract: Lowering temperature rapidly reduced p38 activation and the subsequent p38-regulated production of pro-inflammatory cytokines and NO in ATP-activated microglia, suggesting that attenuation of early phase inflammatory responses via suppression of p38 in microglia is one possible neuroprotective mechanism of therapeutic hypothermia. Temperature elevation increased TNF-α and NO production in these cells. These temperature-dependent changes imply that monitoring of TNF-α and NO in the cerebrospinal fluid during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 40 publications
4
29
0
Order By: Relevance
“…In addition, an ex vivo culture of microglia isolated from CNS preserves the in vivo phenotype of microglia [18,51]. Importantly, as mentioned above, in terms of the temporal changes of neuroinflammatory responses, our present ex vivo findings, as well as our previous in vitro findings [33][34][35][36], appear to be similar to the in vivo findings for brain injury [9,11], as well as to those regarding IL-10 in vivo, which indicate that the levels in the brain show a peak during the first days (24-48 h) after brain injury [6,14,25]. Temporal similarity between the ex vivo and in vivo expressions of a signalling molecule in microglia has also been reported [12,51].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In addition, an ex vivo culture of microglia isolated from CNS preserves the in vivo phenotype of microglia [18,51]. Importantly, as mentioned above, in terms of the temporal changes of neuroinflammatory responses, our present ex vivo findings, as well as our previous in vitro findings [33][34][35][36], appear to be similar to the in vivo findings for brain injury [9,11], as well as to those regarding IL-10 in vivo, which indicate that the levels in the brain show a peak during the first days (24-48 h) after brain injury [6,14,25]. Temporal similarity between the ex vivo and in vivo expressions of a signalling molecule in microglia has also been reported [12,51].…”
Section: Discussionsupporting
confidence: 81%
“…With the aim of elucidating the possible mechanisms underlying the neuroprotective effects of therapeutic hypothermia, we have previously shown that hypothermia reduces the production of earlyphase and late-phase inflammatory factors as well as that of late-phase anti-inflammatory factor in primary microglia in vitro [33][34][35][36]. We considered that an approach using microglia removed directly from injured brains may yield more clinically relevant information.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations